Distinct contributions of cathelin‐related antimicrobial peptide (CRAMP) derived from epithelial cells and macrophages to colon mucosal homeostasis. Issue 3 (19th January 2021) - Chen, Keqiang; Yoshimura, Teizo; Yao, Xiaohong; Gong, Wanghua; Huang, Jiaqiang; Dzutsev, Amiran K; McCulloch, John; O'hUigin, Colm; Bian, Xiu‐wu; Trinchieri, Giorgio; Wang, Ji Ming
Abstract: The cathelin‐related antimicrobial peptide CRAMP protects the mouse colon from inflammation, inflammation‐associated carcinogenesis, and disrupted microbiome balance, as shown in systemic Cnlp −/− mice (also known as Camp −/− mice). However, the mechanistic basis for the role and the cellular source of CRAMP in colon pathophysiology are ill defined. This study, using either epithelial or myeloid conditional Cnlp −/− mice, demonstrated that epithelial cell‐derived CRAMP played a major role in supporting normal development of colon crypts, mucus production, and repair of injured mucosa. On the other hand, myeloid cell‐derived CRAMP potently supported colon epithelial resistance to bacterial invasion during acute inflammation with exacerbated mucosal damage and higher rate of mouse mortality. Therefore, a well concerted cooperation of epithelial‐ and myeloid‐derived CRAMP is essential for colon mucosal homeostasis. © 2020 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.